2019
DOI: 10.1111/echo.14357
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal strain measured by two‐dimensional speckle tracking echocardiography to evaluate left ventricular function in patients with myocardial bridging of the left anterior descending coronary artery

Abstract: Objectives Myocardial bridging (MB) can cause myocardial ischemia, myocardial infarction, or even sudden cardiac death. We aimed to evaluate the left ventricular function in patients with MB of the left anterior descending coronary artery (LAD) using longitudinal strain (LS) measured by two‐dimensional speckle tracking echocardiography. Methods We enrolled 46 subjects with MB in the LAD diagnosed by coronary angiography. Patients were categorized into two groups according to the severity of tunneled artery ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…14 The ratio of early transmitral flow velocity to spectral pulse wave Tissue Doppler imaging (TDI) showed that early diastolic velocity of mitral annulus (E/E') was correlated accurately with the LV filling pressures degree and is a good predictor of the prognosis after the onset of AMI. 15 Our results indicated that E/E'>15 was related to 5-year MACEs. The E/E' ratio should be used to estimate LV filling pressure in AMI patients with impaired or normal LVEF when the transmitral pattern was nonrestrictive and increased LV filling pressure cannot be diagnosed by the simple transmitral flow assessment.…”
Section: Dovepressmentioning
confidence: 50%
“…14 The ratio of early transmitral flow velocity to spectral pulse wave Tissue Doppler imaging (TDI) showed that early diastolic velocity of mitral annulus (E/E') was correlated accurately with the LV filling pressures degree and is a good predictor of the prognosis after the onset of AMI. 15 Our results indicated that E/E'>15 was related to 5-year MACEs. The E/E' ratio should be used to estimate LV filling pressure in AMI patients with impaired or normal LVEF when the transmitral pattern was nonrestrictive and increased LV filling pressure cannot be diagnosed by the simple transmitral flow assessment.…”
Section: Dovepressmentioning
confidence: 50%
“…Notably, this is the first study to confirm that a subtle form of myocardial contractility impairment may be found in patients with MBs, 8 even in the presence of apparently normal cardiac function and OMT. We also demonstrated that surgical unroofing of MBs provides better QoL with less physical limitation and a lower angina frequency than does OMT in adults and adolescents.…”
Section: Discussionmentioning
confidence: 57%
“… 3 , 7 Left ventricular (LV) dysfunction, myocardial stunning, and exercise-induced ventricular tachycardia may also be documented in patients with MBs. 2 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation